An unexpected finding in the resection specimen of a carcinoma of the oral cavity: A case report. (2016) - Olthof, D.C.; Bun, R.J.; Dutrieux, R.P.; Houdijk, A.P.J.
Highlights: The occurrence of two synchronous, primary cancers is rare. Thyroid carcinoma is incidentally found in the resection specimen after surgery for head and neck cancer in 0.3–1.9% of the patients. A papillary thyroid carcinoma was found coincidentally in lymph nodes recovered after a 'commando' procedure for carcinoma of the oral cavity. A tailor made therapeutic approach of incidental thyroid gland carcinoma in head and neck cancer depends on prognosis and life expectancy. Abstract: Introduction: The occurrence of two synchronous, primary cancers is rare. Thyroid carcinoma is incidentally found in the resection specimen after surgery for head and neck cancer in 0.3–1.9% of the patients. Presentation of case: In this report, we describe the case of a 72-year-old patient in whom a primary (synchronous) papillary thyroid carcinoma was found coincidentally upon pathologic examination of lymph nodes recovered from the cervical neck lymph node dissection specimen after a 'commando' procedure for carcinoma of the oral cavity. Discussion and conclusion: There is no gold standard concerning treatment of the incidentally discovered thyroid gland carcinoma. The decision to perform surgery depends on the life expectancy of the patient, whether the thyroid gland demonstrates clinical or radiologic lesions, the already completed treatment for the head and neck cancer and should always be adjusted to the specific patient.